The Impact of Stock Mispricing on Corporate Investment Efficiency. Evidence from the UK Market. - Peng, Xin (2020)
This paper empirically investigates whether stock mispricing can affect investment efficiency in the context of the UK stock market. Firm shareholders hope their capital can get maximum benefits which means that investment efficiency should be high. However, the investment inefficiency problem exists in the majority of firms. Hence, corporate investment efficiency has always been a topic that scholars are concerned about. According to previous literature such as Alzahrani (2006) and Polk and Sapienza (2009), they confirm that stock mispricing affects investment decisions. Therefore, this paper believes that stock mispricing may lead to inefficient investment. The paper follows Biddle et al. (2009) to measure investment efficiency and use M/B decomposition method to calculate the value of stock mispricing. Next, using regression estimates on them to test hypotheses. The pieces of evidence support that stock mispricing is positively correlated with corporate inefficient investment. Moreover, stock overvaluation will significantly increase overinvestment and stock undervaluation has less effect on underinvestment. In addition, this correlation is especially obvious when the degree of stock mispricing is high. Furthermore, the paper finds evidence on a bidirectional relationship between stock mispricing and investment efficiency.